8(1-2h)-(4-10h)+(h-9)=0

Simple and best practice solution for 8(1-2h)-(4-10h)+(h-9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(1-2h)-(4-10h)+(h-9)=0 equation:


Simplifying
8(1 + -2h) + -1(4 + -10h) + (h + -9) = 0
(1 * 8 + -2h * 8) + -1(4 + -10h) + (h + -9) = 0
(8 + -16h) + -1(4 + -10h) + (h + -9) = 0
8 + -16h + (4 * -1 + -10h * -1) + (h + -9) = 0
8 + -16h + (-4 + 10h) + (h + -9) = 0

Reorder the terms:
8 + -16h + -4 + 10h + (-9 + h) = 0

Remove parenthesis around (-9 + h)
8 + -16h + -4 + 10h + -9 + h = 0

Reorder the terms:
8 + -4 + -9 + -16h + 10h + h = 0

Combine like terms: 8 + -4 = 4
4 + -9 + -16h + 10h + h = 0

Combine like terms: 4 + -9 = -5
-5 + -16h + 10h + h = 0

Combine like terms: -16h + 10h = -6h
-5 + -6h + h = 0

Combine like terms: -6h + h = -5h
-5 + -5h = 0

Solving
-5 + -5h = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -5h = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -5h = 0 + 5
-5h = 0 + 5

Combine like terms: 0 + 5 = 5
-5h = 5

Divide each side by '-5'.
h = -1

Simplifying
h = -1

See similar equations:

| 6=0.1x-0.6x-2 | | 23.8=3.2c | | -5x+13=0 | | 9t^2+18t-72=0 | | 2x+13=-4-17 | | 6x^2+5x=8 | | 20+2y-5=12y-10-5y | | y-9=3(x-4) | | y-9=#9x-4) | | -11y+1=-109 | | x^2+y^2+14x-16y+48=0 | | 4a^2+8a=24 | | 0.08(y-9)+0.06y=0.02y-0.09(20) | | 2n+19= | | 3x-5+x=27 | | 20=a(2b+c) | | 2x+1=8(x-3)+6x | | 0.02(7t+6)=0.14(t+3)-0.30 | | -11y+1=109 | | (2x-6)(2x-5)=(4x+1)(x-4) | | 18=-66 | | 18=-66 | | 0.06(y-7)+0.16y=0.04y-0.003(50) | | -20x+100+x^2=0 | | 3(4x-2)-10=5x-2 | | -4x+6=4x+2 | | 3x+6=9X+10 | | 8x-(4x+20)=8 | | 2(h+5)-3(h-2)=5(2h+1) | | 3(x-6)=x-22 | | (25+3x)=(2x+30) | | 17x-114=13x+62 |

Equations solver categories